2016
DOI: 10.1016/j.aap.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting crash–speed relationships: A new perspective in crash modelling

Abstract: Although speed is considered to be one of the main crash contributory factors, research findings are inconsistent. Independent of the robustness of their statistical approaches, crash frequency models typically employ crash data that are aggregated using spatial criteria (e.g., crash counts by link termed as a link-based approach). In this approach, the variability in crashes between links is explained by highly aggregated average measures that may be inappropriate, especially for time-varying variables such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 44 publications
10
59
1
1
Order By: Relevance
“…Road segments are considered as decision making units (DMUs) and the basic target is to identify the best-performing road segments and worst as well. Best are those with minimum output levels given the input exposure variables, and other segments' risk is then measured relative to this frontier [20].…”
Section: Road Accident Risk Index and Benchmarkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Road segments are considered as decision making units (DMUs) and the basic target is to identify the best-performing road segments and worst as well. Best are those with minimum output levels given the input exposure variables, and other segments' risk is then measured relative to this frontier [20].…”
Section: Road Accident Risk Index and Benchmarkingmentioning
confidence: 99%
“…Road segments are considered as decision making units (DMUs) and the basic target is to identify the best-performing road segments and worst as well. Best are those with minimum output levels given the input exposure variables, and other segments' risk is then measured relative to this frontier [20]. Mathematically, to use DEA for road safety evaluation, the model is shown as follows: Mathematically, to use DEA for road safety evaluation, the model is shown as follows:…”
Section: Road Accident Risk Index and Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The model results indicated that average travel speed was not significantly related to crash frequency during the off-peak period, however, during the peak period, a significant positive relationship between average speed and crash frequency was demonstrated. More recently, Imprialou et al (Imprialou et al, 2016) proposed a new condition-based approach to aggregate the crashes according to the similarity of their pre-crash traffic and geometric conditions, and then compared it with the traditional segment-based aggregation approach. The results showed that average speed was significantly positively associated with crash occurrence in the conditionbased model, while the relationship was found to be negative in the segment-based model.…”
Section: Literature Review Aggregated Arterial Safety Analysismentioning
confidence: 99%
“…Though the speed has been considered as one of the leading causes of the accidents, the result of different studies is inconsistent. Imprialou et al [2] modeled a set of data using a multivariable lognormal Poisson regression to indicate part of these inconsistencies. The speed management is an essential strategy for improving the safety on freeways, due to the sharp relationship between speed and accident occurrence and its intensity.…”
Section: Introductionmentioning
confidence: 99%